Anger Expression and the Risk of Cardiovascular Disease Among Urban and Rural Japanese Residents: The Circulatory Risk in Communities Study. Issue 2 (February 2020) - Tezuka, Kazuhide; Kubota, Yasuhiko; Ohira, Tetsuya; Shimizu, Yuji; Yamagishi, Kazumasa; Umesawa, Mitsumasa; Sankai, Tomoko; Imano, Hironori; Okada, Takeo; Kiyama, Masahiko; Iso, Hiroyasu
ABSTRACT: Objective: It has been suggested that urbanization, which has been expanding rapidly for the past several decades, increases the risk of cardiovascular disease (CVD) associated with psychological factors such as anger, but the evidence is limited. We examined the hypothesis that urbanicity modifies the association of anger expression with the risk of CVD. Methods: A prospective study was conducted in 5936 residents of urban and rural communities aged 40 to 79 years who had completed an annual health checkup including a questionnaire on anger expression between 1995 and 1998. Associations of anger expression with the risk of CVDs were examined using Cox proportional hazards models, after adjusting for classical cardiovascular risk factors. Results: During a median follow-up of 16.6 years, we identified 312 incident CVDs. The means (SDs) of anger expression were 24.7 (5.8) among urban residents and 24.6 (5.7) among rural participants ( p = .87). Among urban residents, anger expression was positively associated with the risk of total CVD: the multivariable hazard ratio (95% confidence interval) was 1.27 (1.05–1.54). In contrast, no association was found among rural residents: the corresponding ratio (interval) was 0.96 (0.85–1.09), with a significant interaction between urban and rural residency with anger expression for incident CVD ( p = .047). Similar associations were observed with the risk of CVD subtypes, including ischemic stroke and ischemic CVD. Conclusions: We found a positive association between anger expression and the risk of CVD among urban residents but not rural residents, suggesting that urbanicity enhances the anger-CVD association. Abstract : Supplemental digital content is available in the text.